Stability of an exponentially tapered asymmetric sandwich beam placing on a variable Pasternak Foundation with variable temperature gradient. (March 2021) - Pradhan, Madhusmita; Dash, Pusparaj; Nayak, Dipesh Kumar
The stability investigation of an exponentially tapered sandwich beam, asymmetric in nature placed upon a Pasternak foundation with variable behavior acted upon by a periodic longitudinal load with variable temperature grade with clamped-pinned condition provided at the ends is analyzed in this article. By using Hamilton's energy method, a complete solution for the mathematical modeling of the system is obtained. The equations of motion along with the related boundary conditions are obtained in non-dimensional form. A group of Hill's equations are found by generalized Galerkin's method. Different parameters have significant influence on both the static buckling loads as well as the zones of instability. These effects of these parameters are examined and are presented in a graphical manner. The outcomes resulted due to uniform and variable temperature grade are compared.